2016
DOI: 10.31729/jnma.2809
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic, Epidemiological and Environmental Determinants of Acute Gastroenteritis in Western India

Abstract: Introduction: An outbreak of acute gastroenteritis had occurred in Rajpara village of Bhavnagar district. The objective of this study was to find out the socio-demographic, epidemiological and environmental determinants of this outbreak.Methods: A case-control study was conducted in Rajpara village among 238 cases of acute gastroenteritis and an equal number of controls in January 2015. Multiple logistic regression was used for identifying the variables independently predicting acute gastroenteritis.Results: U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The fact that we did not find a significant association between drinking water coliform counts (total or fecal) and reported GI symptoms was not entirely unexpected, since similar studies in India and Mexico also did not find direct associations between water bacterial indicators and GI symptoms [ 32 , 47 ]. A study in Alabama found that drinking water bacterial indicators were associated specifically with vomiting and diarrhea prevalence, but not with general GI symptoms [ 30 ].…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…The fact that we did not find a significant association between drinking water coliform counts (total or fecal) and reported GI symptoms was not entirely unexpected, since similar studies in India and Mexico also did not find direct associations between water bacterial indicators and GI symptoms [ 32 , 47 ]. A study in Alabama found that drinking water bacterial indicators were associated specifically with vomiting and diarrhea prevalence, but not with general GI symptoms [ 30 ].…”
Section: Resultssupporting
confidence: 48%
“…Studies in other regions have found no correlations between microbial contamination and consumer ratings of water taste [ 28 30 ]. In contrast, de Queiroz et al found that familiarity of the water source characteristics (taste, odor, and color) plays a strong role in consumer preferences and risk perception, and Rupani et al observed that a change in taste of the water was correlated with increased risk of gastrointestinal symptoms [ 31 , 32 ]. In a study of household perceptions of water in Minnesota, Scher et al found that higher manganese concentration was associated with greater concern about taste, odor, or color of the water, but that 54% of respondents whose well water had concentrations of Mn above 300 micrograms per liter ( μ g/L) were not very concerned with the taste, odor, or color of their water [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of conductivity (42.10%), turbidity (62.10%), and iron (82.10%), the majority of the samples' physicochemical characteristics were found to be within the WHO's permissible range, according to Shrestha 2002). In contrast, de Queiroz et al, discovered that familiarity with water source characteristics (taste, odor, and color) influences consumer preferences and risk perception, and Rupani et al, discovered that a change in water taste was associated with an increased risk of gastrointestinal symptoms (Queiroz et al, 2019, andRupani et al, 2016). According to a study of Minnesotan households' perceptions of water by Ocher et al, higher manganese concentrations were linked to greater concern about the taste, odor, or color of the water, but 54% of respondents whose well water had Mn concentrations above 300 micrograms per liter (g/L) were not particularly concerned about those factors (Escheret et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%